A Numerical Approach for Optimization of Curing Kinetics of Composite Material - Öz, Murat; Öz, Murat; Tanoğlu, Gamze (Izmir Institute of Technology, 2021)
In this thesis, we introduced a new method which is called the GMN (Gamze, Murat, Neslişah) algorithm. GMN algorithm determines the pre-exponential and activation energy of the curing process. This algorithm include tanh fitting for the measured conversion values via least squares minimization technique and linear fitting for the kinetic parameters. Experimentally determined differential scanning calorimetry (DSC) data sets for an epoxy resin functionalized by single wall carbon nanotubes are used for the verification of the proposed method. In computational part, in order to denote the effectiveness of the new proposed method, the results are also compared with the methods reported in the literature. To sum up, we have shown that the GMN algorithm provides a good match with the experimental data for all kinetic parameters.

Bu tezde, kürleme işleminin ön üstel ve aktivasyon enerjisini belirlemek için yeni bir algoritma GMN (Gamze, Murat, Neslişah) sunduk. Bu metod ölçülen dönüşüm değerleri için tanh eğri uydurma yöntemi ile en küçük kareler minimizasyon yöntemlerinin kombinasyonun içerir ve kinetik parametre için liner eğri uydurma yöntemi kullanır. Sunulan yöntemin doğrulanması için tek duvarlı karbon nanotüpler tarafından işlevlendirilmemiş bir epoksi reçinesi için deneysel olarak belirlenmiş diferansiyel taramalı kalorimetri (DSC) veri setleri kullanılmıştır. Hesaplama kısmında, önerilen yeni yöntemin etkinliğini belirtmek için sonuçlar literatürde bildirilen yöntemlerle de karşılaştırılmıştır. Son olarak, GMN algoritması, kinetik parametrelerin hesaplanması için deneysel verilerle iyi bir tutarlılık içerinde olduğu elde edilmiştir.
Kompozit Malzemenin Küreltme Kinetiğinin Optimizasyonu için Sayısal Bir Yaklaşım
Thesis (Master)--Izmir Institute of Technology, Mathematics, Izmir, 2021
Includes bibliographical references (leaves. 55-58)
Text in English; Abstract: Turkish and English
Keywords: Composite materials; GMN algorithm; Differential scanning calorimetry; Curing kinetics